Landing biomechanics in classical ballet - Osmala, Johanna (2024)
Objective: The primary aim of this study was to investigate interseason variability in the knee frontal plane projection angle (FPPA) at the impact phase of a single-leg dropjump test in female and male professional ballet dancers. The secondary aim was to explore the effect of leg dominance and ankle dorsiflexion mobility on the FPPA.